Therapeutic Effects of Ethanolic Extract of Polygonum limbatum meism Against Reproductive Toxicity Induced by Cadmium in Male Guinea Pigs (Cavia porcellus) - Menkem, Brice; Vemo, Bertin Narcisse; Tsambou, Megnimeza Martine Astride; Fonou, Tadiesse Lavoisier; Dongmo, Nguedia Arius Baulland; Boufack, Judith Laure; Chongsi, Margaret Mary Momo; Kenfack, Augustave (Frontiers in Veterinary Science, 2021)
This study aimed at evaluating the therapeutic effects of Ethanolic Extract of Polygonum limbatum meism (EEPLM) on the reproductive parameters of male Guinea pig exposed to cadmium chloride. Thirty six (36) male guinea pigs were randomly assigned to six treatment groups (with six animals per group). Group 1 (DW) received distilled water orally; group 2 (Cd) negative control was treated with cadmium chloride at a dose of 26.25 mg/kg body weight.(bw) while group 3 (Vit C) positive control was given 26. 25 mg of cadmium chloride/kg bw and 100 mg of vitamin C and groups 4, 5 and 6 were treated, respectively, with EEPLM at doses of 50, 100 and 200 mg/kg bw in addition to cadmium chloride (26.25 mg/kg bw). After 90 days, all animals were sacrificed and data related to reproduction, toxicity, and oxidative stress were collected. Results revealed a signiﬁcant decrease (p<0.05) of serum level of creatinine, urea, alanine and aspartate amino transferases in guinea pigs treated with cadmium chloride and EEPLM compared to the negative control group (Cd). The weight of bulbourethral gland was significantly (p<0.05) decreased in animals exposed to cadmium chloride and treated with vitamin C or EEPLM compared to the negative control (Cd). Guinea pigs orally receiving cadmium chloride and EEPLM showed significantly (p<0.05) increased motility, sperm count, spermatozoa with entire plasma membrane and percentage of normal spermatozoa with reference to the negative control (Cd). The serum level of testosterone increased insignificantly (p>0.05) in animals given cadmium and EEPLM compared to the negative control (Cd). Animals Co-administered cadmium chloride and EEPLM recorded significantly (p<0.05) reduced level of MDA, activities of SOD and total peroxidases compared to the group that received cadmium chloride (Cd) only. In conclusion, cadmium chloride induced reproductive impairments, by generating oxidative stress. However, the administration of EEPLM can mitigate these adverse effects due to its antioxidant properties.